Sejarah Pancasila Sebagai Salah Satu Awal Sejarah Hukum Di Indonesia - Redyanto Sidi; Hasan Basri; Ahmad Akbar; Irhamuddin Irhamuddin; Nirmayana Sinaga (Iuris Studia: Jurnal Kajian Hukum, 2021)
Pancasila is the ideology of the Indonesia nation as well as asource of law. His becomes very logical because pancasila itself was born because of the existence of the Indonesian nation from time immemorial or since inhabiting the Indonesian islands, thus, it can be said that Pancasila is one part of the early history of law in Indonesia and a source of law in indonesia